2012 Se te vino la noche - Grupo Los que dijeron oh (2017)
Córdoba | Teatro La Cochera | Grupo Los que dijeron oh | Dramaturgia: Daniel Pereyra | Actúan: Dimas Games, Mario Gorostidi, Sergio Ariel Heredia, Jorge Juárez, Javier López, Monica Morea, Leandro Pineda, Verónica Ripoll, Ernesto Salas, Marcelo Trujillo | Operación técnica: Lucas Solé | Dirección: Paco Giménez | Consultado el 18 de septiembre de 2017 | http://www.alternativateatral.com/obra23588-se-te-vino-la-noche